Head impact events in youth football in India and Australia, compared to FIFA Men's World Cup matchesPractical Implications: - Isaac Roman; Marnee McKay; Kerry Peek (Elsevier, 2023)
Summary: Objectives: This observational study compared incidence and characteristics of head impact events in matches in male youth under-18 football within Australia and India, to the Men's FIFA World Cup™ (FWC). Methods: Ten match videos from Australia, India and the 2018 FWC (total n ​= ​30) were coded for head impact events (purposeful headers and unintentional head impacts), match result as well as incidence rates (IR) per 1000 match-hours for heading performance characteristics. One-Way ANOVAs were conducted to assess statistical significance of heading IR and other characteristics. Results: Purposeful headers (n ​= ​2734) were the most common head impact event (97%) with significantly more headers being completed by players from India (IR:3239) compared to Australia (IR: 2096) and FWC (IR: 2509). Most headers were completed during free play, via contact with the players forehead. Heading duels were more common in FWC matches (32%), than those in Australia (23%) or India (19%) (p ​< ​0.001). More headers occurred in the centre of the pitch (range 36-48%), with centre-backs completing the most headers across all groups (range 30-33%). Winning teams in India performed more headers from set-pieces than losing teams (p ​< ​0.001). In FWC matches, winning teams performed more headers in the defensive third compared to losing teams (p ​= ​0.02). Conclusion: Despite similar heading characteristics across both U18 groups and the FWC, players in India recorded higher heading incidence, suggesting that heading guidelines would benefit from being country and age specific.